The crucible : - Miller, Arthur (Penguin books, 1986)
ook Description: Penguin Books, LONDON, 1987. Trade Paperback. Book Condition: Very Good. 12mo - over 6¾" - 7¾" tall. A reprint, published as part of Penguins Modern Classics series. A copy with no creasing to the spine, but light edge wear to the cover and some very light creases adjacent to the spine. The pages are very lightly tanned in what is a clean and tightly bound book. There are no ink inscriptions. A drama based on the witch trials in Salem Village.